Can We Bridge the Gap? Mathematics and the Life Sciences: Part 2 – Discrete Models, Statistics, Co-Curricular Opportunities. Issue 3 (16th March 2022) - Robeva, Raina; Comar, Timothy D.; Eaton, Carrie Diaz
Abstract : This editorial serves as an introduction to Part 2 of the Special Issue Mathematics and the Life Sciences – a collection of articles showcasing ideas, examples, pedagogical frameworks, and curricular materials aiming to bridge the stubbornly persistent gap at the undergraduate level between the mathematical and the life sciences. The special issue features authors from public and private institutions of diverse types, sizes, and geographic locations: community colleges, liberal arts colleges, and research-oriented universities. We hope this special issue will serve as a resource to faculty who seek to make changes to their own course(s) or initiate curriculum reforms at their own schools. This Part 2 special issue features course materials and programs based on discrete mathematics, computational approaches, and statistics. It also includes articles on internship programs and co-curricular opportunities. Part 1 focuses on educational initiatives that are appropriate for calculus classes or require calculus as a prerequisite.